Implementation of Inclusivism Values in Religious Education Learning to Build Human Solidarity at Karuna Dipa High School, Palu - Rusmin, Rusmin; Hamka, Hamka; Ahmad Syahid (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2024)
This research examines the implementation of inclusivism values ​​in religious education learning to build humanitarian solidarity at Karuna Dipa High School, Palu. This research uses qualitative methods, and data is collected through observation, in-depth interviews, and analysis of written documents. The data analysis techniques used are data reduction, presentation, and verification. The research results show that: First, the values ​​of inclusivism are the basic principles at Karuna Dipa High School Palu, namely Inclusive (open) values, tolerance values, mutual help values, justice values, and brotherhood values ​​(humanism). Second, the implementation of inclusivist values ​​in religious education learning at Karuna Dipa Palu High School follows the inclusive religious education learning model from Jack L. Seymour and Tabita K. Cristiani, namely the "beyond the wall" learning model through several integration efforts, namely: 1) Integrated into the Vision and Mission of Karuna Dipa High School Palu, namely "Achievement, Personality and Competitiveness." 2) Integrated into existing religious education learning materials. 3) Integrated in extracurricular activities. 4) Integrated religious holiday celebration activities. Third, the significance of inclusivism in building human solidarity at Karuna Dipa High School in Palu is the following: 1) Building social solidarity between students with different beliefs. 2) Building an attitude of mutual trust in all elements of the school so that a sense of brotherhood is created between students, educators, and the Karuna Dipa Palu Foundation. 3) Forming a competitive spirit with noble moral character in Karuna Dipa High School students.